Digital Activism Resistance Movement in Mining Development Conflict in Wadas Village, Central Java Province - Hamzah Jamaludin (Mahesa Research Center, 2025)
This study aims to analyze the form of resistance of the Wadas Village Nature Care Community Movement (Gempa Dewa) against the andesite rock mining project for the construction of the Bener Dam in Central Java through digital activism. Using a descriptive qualitative approach, data were obtained through in-depth interviews, participatory observations, and documentation studies of various key informants, such as representatives of WALHI Yogyakarta, LBH Yogyakarta, GEMPA DEWA, and local government officials. Data analysis was carried out with Miles and Huberman's interactive model, which included data reduction, data presentation, and conclusion drawn. The results of the study show that the resistance of the Wadas people is born from a sense of injustice due to threats to their ecosystem, livelihoods, and cultural identity. Collective identity, solidarity across generations and genders, and adaptation to digital technology are key factors in strengthening this movement. Digital activism through social media such as Instagram and Twitter is effective in building solidarity networks, expanding the reach of campaigns, and countering the dominant narrative of the government. However, this movement also faces significant challenges, such as digital repression, intimidation, social fragmentation, and lack of public participation in decision-making.